Impact of Islam on the History of Karnataka - Dr. V. VENKATESH (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
Soon after Islam’s propagation in Arabia, as Arabs were trading at the ports of Karnataka like Mangalore, Bhatkal and few others, Islam entered Karnataka in the 7th century A.D. The Persian ruler Khusru-II established diplomatic relations with King Pulikesi-II of the Chalukyas of Badami (535 - 757 A.D.). Some of the Arabshad settled on the West Coast of Karnataka and inscriptions speak of them as Tajjikas. The Rashtrakutas (757-1000 A.D.) had a Tajjika governor at Konkan as testified by Sanjan plates, and Arab travellers also speak of Muslim settlements in the major commercial centres of the Rashtrakuta Empire. Their guild called Hanjamana (Anjuman) is mentioned in the records of the Kadambas of Goa, Alupas of Dakshina Kannada and Vijayanagara rulers. This guild Hanjamana was part and parcel of every town assembly. Islam also became popular in Karnataka during the Vijayanagara period (1346-1565 A.D.), as the empire employed Muslim soldiers, and all towns and villages in the empire had Muslim residents as testified by Barbosa. (Kamath,1982:430- 431) The Bahamanis werethe first Muslim rulers to enter Karnataka and to have ruled the Northern areas. They were followed by the Adil Shahis, Barid Shahis, Mughals, Haider and Tipu Sultan.